DATA FOR ASSESSMENT OF SENIOR SECONDARY SCHOOL BIOLOGY TEACHERS' AND STUDENTS' PRACTICES RELATED TO COVID-19 IN OYO STATE, NIGERIA (2023)
COVID-19 is a disease caused by a virus called Severe Acute Respiratory Syndrome Coronavirus 2 (SARS – CoV-2) which affected all sectors of human endeavours (including the education sector) globally and resulted in the loss of lives. Owing to this, the World Health Organization (WHO) on the 11th of March 2020, declared the disease a global pandemic. In the same vein, the Nigeria Centre for Disease Control (NCDC) disseminated requisite information on appropriate practices relating to the disease to its populace. This study is therefore designed to assess senior secondary school Biology teachers’ and students’ practices related to COVID-19 in Oyo State, Nigeria. The study adopted a descriptive research survey design with two research questions, and one research hypothesis. The sample size of the study included 620 Biology students (31 students per school) and 20 Biology teachers (1 teacher per school) from 20 senior secondary schools across 5 five Local Government Areas in Oyo State. Two research instruments were used to collect data from respondents, these were Teachers’ Practices related to COVID-19 Test (r = 0.9), and Students’ Practices related to COVID-19 Test (r = 0.85). The data were analysed using descriptive statistics such as per centage (%), mean, and standard deviation; and inferential statistics such as Pearson Product-Moment Correlation Coefficient. This study revealed that there were high levels of Biology teachers’ and students’ proactive practices (74.11% and 62.68% respectively) related to COVID-19 that had a strong positive relationship which is significant (r = 0.69; p<0.05) between them. Conclusively, the study revealed that teachers’ and students’ participants had good practices related to COVID-19. It is an assurance that the participants were proactively prepared in relation to the disease if there should be a resurgence. To improve on the current state of Biology teachers’ and students’ preparedness it was therefore recommended that the government should innovate the current senior secondary school Biology curriculum by including contents that will appreciably help teacher and students have necessary knowledge on protective practices regarding the viruses; train teachers on COVID-19; and include Information and Communication Technology in all public schools’ academic activities.